Preincubation of Mesorhizobium ciceri with flavonoids improves its nodule occupancy - Sharma, P K; Upadhyay, K K; Kamboj, D V; Kukreja, K (Folia microbiologica, 2002)
Strains of M. ciceri, symbionts of chickpea (Cicer arietinum) were incubated with the flavonoids naringenin, daidzein and quercetin which have earlier been reported as inducers and inhibitors of nodABC-lacZ fusion of M. ciceri. Preincubation of M. ciceri with naringenin and daidzein (100 nmol/L) for 1 d improved the competitive ability of the inoculated strain while preincubation with quercetin decreased the nodule occupancy of inoculated strain under sterile conditions. Under non-sterile conditions induced strains of Rcd 301 and HT-6 formed by 23 and 18% more nodules, respectively, than untreated control. Quercetin-treated strains showed by 13-20% fewer nodules than untreated controls. Therefore, it is possible to regulate the competitive ability of inoculated strains by flavonoid treatment.
Keywords: symbióza; Alphaproteobacteria; bakteriální proteiny; Flavanones; kořeny rostlin; Isoflavones; Plant Roots; isoflavony; Quercetin; Flavonoids; Symbiosis; Bacterial Proteins; flavonoidy; Cicer; flavanony; regulace genové exprese u bakterií; quercetin; Gene Expression Regulation, Bacterial